Insertion of Ecuador to the Pacific Basin. What should we expect from the new government? - Roca, Sonia (2016)
The author states that, unlike the Asian actors who are able of moving within the politics defined by regional organisms, Latin American multilateral institutions are not efficient enough so as to fulfill their mediating role in the relations towards the Asian-Pacific area. In designing foreign policies towards the Asian countries, Ecuador should not worry about such factors as geographical extension, population size or scale economies. The opportunities are in the development of an amplified market between the Asian and Andean Regions.